H3ABioNet computational metagenomics workshop in Mauritius: training to analyse microbial diversity for Africa. Issue 1 (December 2015) - Baichoo, Shakuntala; Botha, Gerrit; Jaufeerally-Fakim, Yasmina; Mungloo-Dilmohamud, Zahra; Lundin, Daniel; Mulder, Nicola; Promponas, Vasilis; Ouzounis, Christos
Abstract In the context of recent international initiatives to bolster genomics research for Africa, and more specifically to develop bioinformatics expertise and networks across the continent, a workshop on computational metagenomics was organized during the end of 2014 at the University of Mauritius. The workshop offered background on various aspects of computational biology, including databases and algorithms, sequence analysis fundamentals, metagenomics concepts and tools, practical exercises, journal club activities and research seminars. We have discovered a strong interest in metagenomics research across Africa, to advance practical applications both for human health and the environment. We have also realized the great potential to develop genomics and bioinformatics through collaborative efforts across the continent, and the need for further reinforcing the untapped human potential and exploring the natural resources for stronger engagement of local scientific communities, with a view to contributing towards the improvement of human health and well-being for the citizens of Africa.